Strategies and technologies for developing online computer labs for technology-based courses - Chao, Lee 1951-; Gale Group (Hershey, Penn. IGI Pub., 2008)
"Discusses design strategies, implementation difficulties, and the effectiveness of online labs. Provides scholars, researchers, and practitioners support for lab-based e-learning, gives guidance on the selection of technologies for various projects, and illustrates Web-based teaching with case studies"--Provided by publisher.
Preface -- Acknowledgement -- Section I: Introduction -- Section II: Design of online computer labs -- Section III: Development of online computer labs -- Section IV: Management of online computer labs -- Section V: Trends and advances -- Conclusion -- References.
Keywords: Computer networks -- Design and construction; Instructional materials centers -- Design and construction; Schools -- Computer networks -- Design and construction; Educational technology; Web-based instruction; Electronic books